Nox5 and the Regulation of Cellular Function - Fulton, David J.R. (Mary Ann Liebert, Inc., 2009)
The NADPH oxidase (Nox) family of enzymes is comprised of seven members, Noxes 1–5 and the Duoxes 1 and 2. Nox5 was the last of the conventional Nox enzymes to be identified, and in comparison to its siblings, much less is known about its molecular regulation and even less regarding its functional significance. The loss of Nox5 from rodent genomes has contributed significantly to this deficit in knowledge, but recent discoveries have narrowed the gap. There are many differences between Nox5 and the other Nox isoforms including alternative splicing, transcriptional regulation, enzymatic control mechanisms, tissue distribution, and intracellular trafficking. The goal of this review is to outline recent advances in our knowledge of the genetic regulation, the molecular mechanisms governing its activity, and the functional significance of Nox5 in human physiology and pathophysiology. Antioxid. Redox Signal. 11, 2443–2452.